A MODEL FOR INCREASING REFORM IMPLEMENTATION AND TEACHER EFFICACY: TEACHER PEER COACHING IN GRADES 3 AND 6 MATHEMATICS - Bruce, Catherine; Ross, John (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
This study examined the effects of peer coaching on mathematics teaching practices and teacher beliefs about their capacity to have an impact on student learning. Twelve teachers in grades 3 and 6 participated in a brief but intensive professional development program over six months. The program focused on effective math‐ ematics teaching strategies and peer coaching opportunities. Data sources included classroom observations, teacher self‐assessments, interviews, and field notes. Data were analysed using a two‐level qualitative coding strategy with multiple inter‐ preters. Findings showed that teachers implemented key strategies for effective mathematics teaching, especially in facilitating student interaction and improving the quality of tasks assigned. Key words: mathematics, teaching strategies, professional development Cette étude a trait aux effets de l’enseignement mutuel en mathématiques sur les méthodes pédagogiques des enseignants et leurs croyances quant à leur capacité d’avoir un impact sur l’apprentissage de leurs élèves. Douze enseignants en 3e et 6e années ont participé à un programme de perfectionnement intensif sur une période de six mois. Le programme était axé principalement sur des stratégies efficaces pour l’enseignement des mathématiques et les possibilités d’enseignement mutuel. Les sources des données étaient multiples : observation de la classe, auto‐évaluation de l’enseignant, entrevues et notes prises sur le terrain. Les données ont été analysées à l’aide d’une stratégie de codage qualitatif à deux niveaux avec de multiples interprètes. Les résultats indiquent que les enseignants ont mis en œuvre des stratégies clés pour enseigner efficacement les mathématiques, notamment en facilitant les interactions entre les élèves et en améliorant la qualité des tâches assignées. Mots clés : mathématiques, stratégies pédagogiques, perfectionnement professionnel.